Implementasi Pembelajaran Matematika Melalui Model Problem Based Learning Berbasis Numbered Heads Together Ditinjau Dari Penalaran Matematis Siswa(Penelitian Eksperimen pada Kelas VII Semester Genap MTs NegeriSurakarta II Tahun Ajaran 2015/ 2016) - Agusyati, Dwi Rosita (2016)
The aim of research to describe and analyze: (1) the effect of mathematics learning with model Problem Based Learning and Problem Based Learning based Numbered Heads Together for mathematics learning outcome, (2) the effect of mathematical reasoning for mathematics learning outcome, (3) the interaction between learning models and mathematical reasoning for mathematics learning outcome. Research conducted a quasi experimental research. The population of the research was all students of VII Grade of MTs Negeri Surakarta II of even semester of academic year 2015/2016. The sampling technique used is cluster random sampling. Methods of data collection use test and documentation. Data analyzed technique by two-way analysis of variance a cell is not the same. The results of data analysis with a significance level of 5% was obtained: (1) There is effect of mathematics learning with model Problem Based Learning and Problem Based Learning based Numbered Heads Together for mathematics learning outcome, with (2) There is effect of mathematical reasoning for mathematics learning outcome, with (3) There is no interaction between between learning models and mathematical reasoning for mathematics learning outcome, with .